Studi Literatur Kebijakan Pengelolaan Lingkungan dalam Kegiatan Pertambangan Batuan di Kabupaten Gorontalo - Suryadi Syamsuddin; Marini Susanti Hamidun; Dewi Wahyuni K. Baderan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Rock mining is a key sector contributing to economic development, including in Gorontalo Regency. However, this activity often generates negative environmental impacts such as erosion, water pollution, and ecosystem degradation. This study aims to analyze environmental management policies in rock mining activities using a literature review approach. The research was conducted by examining relevant literature published in the last five years, including national and regional regulations, as well as case study reports. The findings reveal that Indonesia has established a comprehensive regulatory framework through Law No. 32 of 2009 and Government Regulation No. 22 of 2021, which mandate Environmental Impact Assessment (AMDAL) as a key instrument for environmental protection. At the regional level, Gorontalo Provincial Regulation No. 2 of 2019 serves as the main guideline; however, its implementation faces challenges such as weak oversight and inadequate law enforcement. A case study in Motoduto Village shows actual environmental impacts in the form of erosion and sediment load increases in the Paguyaman River, although still within acceptable limits. Additionally, some companies operate without proper AMDAL or legal permits. Therefore, strengthening institutional capacity, digitizing permit data, and engaging communities are essential steps. Policy recommendations include consistent law enforcement, implementation of post-mining reclamation, and integration of spatial data-based policies. This study underscores the importance of a holistic approach to ensure a balance between the economic benefits of the mining sector and environmental conservation.